QCD Higher-Order Effects and Search for New Physics - Wang, Jian (Springer Theses, Recognizing Outstanding Ph.D. Research, 2016)
This book mainly investigates the precision predictions on the signal of new physics at the Large Hadron Collider (LHC) in the perturbative Quantum Chromodynamics (QCD) scheme. The potential of the LHC to discover the signal of dark matter associated production with a photon is studied after including next-to-leading order QCD corrections.The factorization and resummation of t-channel top quark transverse momentum distribution in the standard model at both the Tevatron and the LHC with soft-collinear effective theory are presented. The potential of the early LHC to discover the signal of monotops is discussed. These examples illustrate the method of searching for new physics beyond what is known today with high precision.